Assessing Pedestrian Accessibility to Green Space Using Gis - Tudor MORAR; Radu RADOSLAV; Luiza Cecilia SPIRIDON; Lidia PĂCURAR (Transylvanian Review of Administrative Sciences, 2014)
This paper aims at comparing the parameter of green space per capita currently requested by the Romanian legislation to accessible green space per capita. The comparison is undertaken through a Geographic Information System methodology that uses publicly available data to evaluate actual population numbers with pedestrian access to parks and green squares. Using the city of Timișoara as a case study, population is divided into three main groups according to neigh borhood type in order to investigate the urban planning implications of residential typologies in relation to green space. Two scenarios are compared, namely the existing situation which describes access to municipally-administered parks and squares and the possible situation where both existing and informal green spaces are considered. The main findings show that, at present, only a quarter of the city’s population benefits from proper access, yet by developing all residual green areas this proportion could be raised to over 40%. However, the current parameter of square meters per person requested by the Romanian legislation proves to be insufficient in indicating green space accessibility because of the uneven distribution of population and green areas across the city.